Forming the suburban zone of the great seaside city - Yavorska, Viktoriya; Onufrіеnko, Vyacheslav (Journal of Education, Health and Sport, 2019)
The article looks at the problems of formulating the primitive zone of the Great Primorsky Mist. From the article it was stated that the planning scheme for the territory of the Odessa region needs to be developed, in fact, a new direction - the functional zoning of water areas adjacent to the agglomeration, and estuaries, as well as lands of the water fund, which are allocated in the Water and Land codes of Ukraine, but have not yet been allocated to terrain (in kind). The general scheme of separation of the sea from the coastal zone is already known. But it must be substantially detailed in relation to the natural features of the coast and the socio-economic needs of theOdessaagglomeration andUkraineas a whole.